Implementasi Pembelajaran Make a Match untuk Meningkatkan Kreativitas Pembelajaran Siswa Kelas X di SMA Negeri 2 Kampar Kiri Tengah pada Mata Pelajaran Biologi dengan Pokok Bahasan Pencegahan dan Pengobatan Infeksi Virus - Rosanti, Fitria (Medan Resource Center, 2023)
This research concentrates on enhancing learning creativity among class X students at SMA Negeri 2 Kampar Kiri Tengah. Conducted as classroom action research across two cycles, involving planning, action implementation, observation, and reflection. The study, encompassing 15 class X students, reveals the efficacy of the